Truncated isoform Vav3.1 is highly expressed in ovarian cancer stem cells and clinically relevant in predicting prognosis and platinum‐response. Issue 8 (14th December 2017) - Reimer, Daniel; Boesch, Maximilian; Wolf, Dominik; Marth, Christian; Sopper, Sieghart; Hatina, Jiri; Altevogt, Peter; Parson, Walther; Hackl, Hubert; Zeimet, Alain G.
Abstract : Vav3 is a key modulator of GTP‐hydrolases of the Rho/Rac family, which are crucially involved in cell proliferation. Vav3 is alternatively spliced in full‐length Vav3‐alpha and N‐terminal truncated Vav3.1 lacking its self‐regulatory domains. The aim of our study was to estimate the clinical impact of Vav3 and all other Vav family members in ovarian cancer. Purification of a stem‐cell like side‐population (SP) from ovarian cancer cell lines was performed by flow cytometry/FACS. Differences in gene expression between SP and NSP were assessed by Gene Array analysis and confirmed by RT‐PCR and immunoblot. In addition, Vav mRNA expression was determined in 150 epithelial ovarian cancers. Clinicopathological parameters, platinum‐sensitivity and survival were analyzed and associated with Vav expression. SP fractions of ovarian cancer cell lines exhibited marked overexpression of Vav3.1 ( p < 0.001). Vav1 and Vav2 did not prove to be of clinicopathologic relevance in ovarian cancer. High Vav3.1 expression correlated with higher FIGO stage and residual disease. Furthermore, Vav3.1 overexpression was associated with poor progression‐free (HR = 2.820, p = 0.0001) and overall survival (HR = 2.842, p = 0.0001). Subgroup analyses revealed an impact of Vav3.1 on survival in Type‐II but not in Type‐I cancers. Notably, platinum‐refractory cancers showed marked overexpression of Vav3.1 compared to other subsets of platinum‐sensitivity (15.848 vs . 6.653, p = 0.0001). In conclusion, Vav3.1 is over‐expressed in stem‐cell like SP fractions and is clinically relevant in the pathophysiology of ovarian cancer. The N‐terminal truncated Vav3.1 may be decisively involved in mechanisms causing genuine multi‐drug resistance. Abstract : What's new? Ovarian cancer is the most lethal gynecologic cancer in Western countries. Platinum resistance is a major obstacle for sufficient treatment, though understanding of the mechanisms involved in platinum resistance is incomplete. Our study shows that the N‐terminal truncated Vav3.1 isoform, produced by alternative splicing of Vav3, a modulator of GTP hydrolases of the Rho/Rac family, is overexpressed in multi‐drug resistant stem‐cell like fractions of ovarian cancer cells. Vav3.1 expression was significantly higher in platinum‐refractory ovarian cancers compared to other ovarian cancer specimens, with marked overexpression in ovarian tumors with genuine but not acquired platinum resistance.